2007
DOI: 10.2522/ptj.20060006
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic Physical Therapy for Hip and Knee Osteoarthritis: Results of a Single-Blind Randomized Controlled Trial

Abstract: Compared with no intervention, a 6-week program of aquatic physical therapy resulted in significantly less pain and improved physical function, strength, and quality of life. It is unclear whether the benefits were attributable to intervention effects or a placebo response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
215
2
23

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(253 citation statements)
references
References 35 publications
13
215
2
23
Order By: Relevance
“…For example, visual analog scales are commonly used scales but vary in respect to the targeted pain. That is, bodily pain (Wang et al, 2007), pain during rest and walking (Lund et al, 2008), and joint specific pain (Cochrane et al, 2005;Hinman et al, 2007) have all been assessed with different outcomes. The present study assessed the joint specific pain immediately before and after the exercise.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, visual analog scales are commonly used scales but vary in respect to the targeted pain. That is, bodily pain (Wang et al, 2007), pain during rest and walking (Lund et al, 2008), and joint specific pain (Cochrane et al, 2005;Hinman et al, 2007) have all been assessed with different outcomes. The present study assessed the joint specific pain immediately before and after the exercise.…”
Section: Discussionmentioning
confidence: 99%
“…For example, being able to objectively control exercise intensity between two modes of exercise (e.g., water versus land) may allow researchers to determine if differences in therapy outcomes are due to the environmental intervention itself or due to differences in exercise intensity. Previous research examining the effectiveness of aquatic therapy exercise in comparison with land based exercise in OA patients have not used an underwater treadmill, and therefore, have not been able to control water depth and gait speed (Ahern, Nicholls, Simionato, Clark, & Bond, 1995;Cochrane, Davey, & Matthes-Edwards, 2005;Foley, Halbert, Hewitt, & Crotty, 2003;Hinman et al, 2007;Lund et al, 2008;Norton, Hoobler, Welding, & Jensen, 1997;Wang, Belza, Thompson, Whitney, & Bennett, 2007;Wyatt, Milam, Manske, & Deere, 2001). We would postulate that some of the mixed results reported in the literature (Hinman et al, 2007;Lund et al, 2008;Wang et al, 2007) may in part be related to this lack of control over exercise intensity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is insufficient evidence from quality studies to support the use of these tests in this population. Given that balance deficits are associated with hip OA (40 -42) and balance tests are used as outcome measures in intervention studies (40,43,44), further research investigating the measurement properties of balance tests in people with hip OA is recommended.…”
Section: Dobson Et Almentioning
confidence: 99%
“…The National Foundation for Arthritis in United States suggested a water exercise program in 1997 to improve the quality of life in the community of the elderly patients with arthritis 43 . Heywood and Hinman (2007) also demonstrated that water exercise programs has proved effective in relieving the pain and improving the quality of life for the elderly with chronic illnesses by strengthening the muscles around the joints and lifting the pressure off them 44 . In South Korea, a study conducted byKang (2008) indicated that water exercise programs have been extensively administered in recent years for treating the chronic elderly illnesses like discopathy, and osteoarthritis 45 .Wang et.al.…”
Section: Volume 56mentioning
confidence: 99%